2017
DOI: 10.4049/jimmunol.1601596
|View full text |Cite
|
Sign up to set email alerts
|

A New Immunomodulatory Role for Peroxisomes in Macrophages Activated by the TLR4 Ligand Lipopolysaccharide

Abstract: Peroxisomes are proposed to play an important role in the regulation of systemic inflammation; however, the functional role of these organelles in inflammatory responses of myeloid immune cells is largely unknown. In this article, we demonstrate that the nonclassical peroxisome proliferator 4-phenyl butyric acid is an efficient inducer of peroxisomes in various models of murine macrophages, such as primary alveolar and peritoneal macrophages and the macrophage cell line RAW264.7, but not in primary bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…The genes were applied to enrichment analysis and they were significant enriched in 11 terms (Figure 8B). Interestingly, except peroxisome, several immune-related processes including phagocytosis, regulation of adaptive immune response, regulation of lymphocyte mediated immunity, and ECM affiliated were enriched, consistent with the associations of peroxisomes with immune response and inflammation reported in previous studies (Vijayan et al, 2017;Di Cara et al, 2019), indicating the implication of HSD17B4, ACAA1, and PXMP4 in these processes.…”
Section: Nsclc Specific Network Of Hsd17b4 Acaa1 and Pxmp4 And Theisupporting
confidence: 88%
“…The genes were applied to enrichment analysis and they were significant enriched in 11 terms (Figure 8B). Interestingly, except peroxisome, several immune-related processes including phagocytosis, regulation of adaptive immune response, regulation of lymphocyte mediated immunity, and ECM affiliated were enriched, consistent with the associations of peroxisomes with immune response and inflammation reported in previous studies (Vijayan et al, 2017;Di Cara et al, 2019), indicating the implication of HSD17B4, ACAA1, and PXMP4 in these processes.…”
Section: Nsclc Specific Network Of Hsd17b4 Acaa1 and Pxmp4 And Theisupporting
confidence: 88%
“…We could speculate that lipid metabolism, fatty acid synthesis and degradation in particular, might support a protective microglia phenotype, which could drive neuroprotection in neurodegenerative diseases. Furthermore, as we previously showed that peroxisomal FAO is a hallmark of M2 macrophages [73], and considering the novel roles of peroxisomes in immune cell functioning [74][75][76][77], it is of importance to also highlight this aspect of metabolism in microglia. In our study, we observed, in contrast to macrophages, no changes in peroxisomal FAO in polarized microglia.…”
Section: Discussionmentioning
confidence: 97%
“…After repeating the extraction and centrifugation twice, the supernatants were combined and diluted with 7 mL of water. For some experiments, the sample was further purified with a polymeric reversed phase SPE cartridge as described previously . Briefly, the cartridge was first equilibrated with 3.5 mL of 100% methanol followed by 3.5 mL of water; then the sample was loaded and washed with 10% methanol; neurosteroids were eluted from the cartridge with 1.5 mL of methanol.…”
Section: Methodsmentioning
confidence: 99%
“…For some experiments, the sample was further purified with a polymeric reversed phase SPE cartridge as described previously. 47 Briefly, the cartridge was first equilibrated with 3.5 mL of 100% methanol followed by 3.5 mL of water; then the sample was loaded and washed with 10% methanol; neurosteroids were eluted from the cartridge with 1.5 mL of methanol. After evaporating the solvent from the eluate in a nitrogen stream, the residue was reconstituted in 200 μL of methanol.…”
Section: Sample Preparationmentioning
confidence: 99%